REFLEKSI PENGGUNAAN ARTIFICIAL INTELLIGENCE SEBAGAI MEDIA PEMBELAJARAN DALAM PENDIDIKAN ISLAM - Nur Fadhillah, Annisa; Syafitri, Falya Rahmatika; Faizin, Moh. (Fakultas Agama Islam Universitas Kutai Kartanegara Tenggarong, 2025)
The rapid development of technology has made humans more dependent on and preferring instant things, and one of the technologies that is developing rapidly at this time is Artificial Intelligence. In the world of education, Artificial Intelligence provides interactive and adaptive learning methods according to the needs of the learning process. Regarding Artificial Intelligence as a learning medium in Islamic education, it is essential to explore opportunities, challenges, and directions for educational development that can combine technological advances with Islamic values. The use of Artificial Intelligence as a learning medium in Islamic education helps the continuity of the teaching and learning process, but educators and students must not completely rely on Artificial Intelligence and must remain steadfast in Islamic teachings. Carrying out activities outside the boundaries of the use of Artificial Intelligence is one of the main challenges in the implementation of Islamic education learning. The purpose of this study is for readers to understand the role of Artificial Intelligence and reflections on its use as a learning medium.